Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.amjcard.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myocardial Perfusion Pattern on Frequency and Severity of Mitral Regurgitation in Patients With Known or Suspected Coronary Artery Disease

Abstract: Mitral regurgitation (MR) is common with coronary artery disease (CAD), as altered myocardial substrate can impact valve performance. SPECT myocardial perfusion imaging (MPI) enables assessment of myocardial perfusion alterations. This study examined perfusion pattern in relation to MR. 2377 consecutive patients with known or suspected CAD underwent stress MPI and echocardiography (echo) within 1.6±2.3 days. MR was present on echo in 34% of patients, among whom 13% had advanced (≥moderate) MR. MR prevalence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
(18 reference statements)
2
16
0
1
Order By: Relevance
“…Attenuation correction imaging and/or prone reposition imaging (as clinically tolerated) was used to differentiate between pathologic perfusion deficits and attenuation artifact in accordance with previously employed methods. 12, 15 Post-stress images were acquired approximately 30 minutes following exercise, and 1–2 hours following pharmacologic stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation correction imaging and/or prone reposition imaging (as clinically tolerated) was used to differentiate between pathologic perfusion deficits and attenuation artifact in accordance with previously employed methods. 12, 15 Post-stress images were acquired approximately 30 minutes following exercise, and 1–2 hours following pharmacologic stress.…”
Section: Methodsmentioning
confidence: 99%
“…Regional LV perfusion was assessed using uniform partitions (see Figure 1), whereby LV was partitioned into three equal size (anterior, inferior and lateral) territories, in accordance with prior methods as employed by our group 15, 19 : Summed stress, rest, and difference scores in each territory were calculated as the sum of individual perfusion scores within encompassed segments. Perfusion territories were not mutually exclusive; patients with defects in multiple territories were scored for each territory based on extent and severity of constitutive segmental deficits.…”
Section: Methodsmentioning
confidence: 99%
“…290,291 Patients whose IMR will improve with revascularization of ischaemic, but viable, subpapillary muscle myocardium alone 292 are being predicted using advanced cardiac perfusion imaging. 293 …”
Section: Ischaemic Mitral Regurgitationmentioning
confidence: 99%
“…Previously, they have looked at such features as delayed enhancement MRI to detect subclinical infarction of the papillary muscles. Their interest in perfusion as it relates to the presence of ischemic mitral regurgitation was elegantly demonstrated in their recent manuscript that clearly demonstrated that the myocardial perfusion pattern in left ventricular segments adjacent to the papillary muscles influenced both the presence and the severity of MR in a cohort of over 2000 patients [5]. In the current study, the authors extended their findings to explore the relationship between myocardial perfusion pattern and magnitude of mitral regurgitation in patients undergoing PCI.…”
mentioning
confidence: 69%